Implementasi Sistem Pelayanan Rakyat Sidoarjo di Desa Gempolsari Kecamatan Tanggulangin Kabupaten Sidoarjo - Saffana, Amelia Nur; Rodiyah, Isniaini (Jurnal Noken: Ilmu-Ilmu Sosial, 2025)
This research aims to find out how the SIPRAJA program is implemented as a form of innovation and realization of smart governance in the government of Gempolsari Village, Tanggulangin District, Sidoarjo Regency. This research uses descriptive research with qualitative research methods and data collection techniques in the form of interviews, documentation and observation. The results of the study show that the Sidoarjo People's Service System (SIPRAJA) in Gempolsari Village, Tanggulangin District, Sidoarjo Regency, from the communication factor, requires consistency by the village government in carrying out continuous outreach regarding the SIPRAJA application. From the resource factor, the Gempolsari Village government needs to consider adding staff to support the SIPRAJA application services. From the disposition factor, it is good, the village government has carried out its duties by carrying out tasks optimally, responsibly, and not half-heartedly even without additional incentives. For bureaucratic structure factors, there needs to be a review of the flow in the document verification process between sub-district and village governments so that it is more structured and reduces overlapping responsibilities.